Design at Mayo - Canales, Rodrigo; Drenttel, William (London : SAGE Publications Ltd, 2017)
In the early 2000s, Mayo Clinic physician Nicholas LaRusso began asking himself a question: if we can test new drugs in clinical trials, can we also test new kinds of doctor-patient interactions?Although over the last 50 years there had been enormous advances in diagnosing and treating disease, the systems of delivering health care had changed little. In fact, new tests, treatments, and procedures meant that the health care experience had become increasingly complex for provider and patient alike.
Originally published: Canales, R., & Drenttel, W. (2010). Design at Mayo. 09-034. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://vol10.cases.som.yale.edu/design-mayo.
Description based on XML content.
Keywords: elektronické knihy; electronic books; LaRusso, Nicholas; Physician and patient -- United States -- Case studies; Physicians -- Psychology -- Case studies; Medical care -- United States